Effects of pericapsular nerve group block and fascia Iliaca compartment block on postoperative analgesia and early rehabilitation in elderly patients undergoing total hip arthroplasty - Fenglei Li; Tao Liao; Jianhua Huang; Ronghua Xu (BMC Surgery)
Abstract Background Total hip arthroplasty (THA) is a common procedure in elderly patients that requires effective postoperative analgesia to enhance recovery and minimize complications. This study compares the effects of pericapsular nerve group block (PENG) and fascia iliaca compartment Block (FICB) on postoperative analgesia and early rehabilitation in elderly patients undergoing THA. Methods This retrospective observational study was conducted from January 2021 to December 2023 and included 216 elderly patients scheduled for THA. Patients were divided into two groups: PENG (n = 108) and FICB (n = 108). The efficacy and safety of the nerve blocks were assessed by procedure and onset times, intraoperative anesthetic use, postoperative pain (VAS scores), analgesic consumption, motor function recovery (Modified Bromage Scores), and adverse reactions. Statistical analysis was performed using SPSS software. Results The PENG group required significantly lower doses of propofol (327.3 ± 90.5 mg vs. 353.4 ± 85.7 mg, p = 0.03) and remifentanil (1.1 ± 0.4 mg vs. 1.4 ± 0.5 mg, p < 0.001) than the FICB group. Postoperative VAS pain scores were lower in the PENG group at 8 h during activity (1.1 vs. 2.1, P < 0.05). The PENG group also showed fewer effective PCA presses (3.5 ± 1.4 vs. 4.3 ± 1.5, p < 0.001) and lower sufentanil consumption (62.3 ± 13.3 µg vs. 72.1 ± 13.6 µg, p < 0.001). The PENG group had a significantly lower incidence of quadriceps weakness (7% vs. 24%, p < 0.001) and faster recovery of motor function at all time points. Conclusions Both PENG and FICB provided effective perioperative analgesia in elderly patients undergoing THA. However, PENG may offer advantages in reducing postoperative pain during activity and in preserving lower limb motor function, potentially facilitating earlier rehabilitation.